Intelligent Coordinated Self-Optimizing Handover Scheme for 4G/5G Heterogeneous Networks - Abdulraqeb Alhammadi; Wan Haslina Hassan; Ayman A. El-Saleh; Ibraheem Shayea; Wasan Kadhim Saad; Hafizal Mohamad (Elsevier, 2024)
Indexed by WOS/ Scopus